2017
DOI: 10.1002/phar.1912
|View full text |Cite
|
Sign up to set email alerts
|

Valproate Protein Binding Is Highly Variable in ICU Patients and Not Predicted by Total Serum Concentrations: A Case Series and Literature Review

Abstract: Protein binding of valproate was highly inconsistent in this cohort of ICU patients, and total valproate concentrations did not predict free concentrations, even when correcting for albumin. Additional research to define best practice for dosing and monitoring valproate and the relationship between free valproate concentrations and clinical or adverse effects in ICU patients is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 40 publications
3
54
0
1
Order By: Relevance
“…Valproate is highly bound to albumin (generally more than 90%) in a concentration‐dependent manner. The free fraction of valproate may be elevated in the setting of hypoalbuminemia, uremia, drugs known to displace it from albumin (e.g., aspirin, ibuprofen, propofol, clevidipine, and intravenous fat emulsion), and at the upper end of its reference range due to albumin binding site saturation . Table summarizes valproate's pharmacokinetic properties.…”
Section: Valproatementioning
confidence: 99%
See 4 more Smart Citations
“…Valproate is highly bound to albumin (generally more than 90%) in a concentration‐dependent manner. The free fraction of valproate may be elevated in the setting of hypoalbuminemia, uremia, drugs known to displace it from albumin (e.g., aspirin, ibuprofen, propofol, clevidipine, and intravenous fat emulsion), and at the upper end of its reference range due to albumin binding site saturation . Table summarizes valproate's pharmacokinetic properties.…”
Section: Valproatementioning
confidence: 99%
“…Free serum concentrations, which represent the amount of drug available for effectiveness, toxicity, and metabolism, should be considered in patients at risk for altered protein binding. Free serum valproate concentration has been associated with neurotoxicity, hyperammonemia, and thrombocytopenia . A study of 15 adult ICU patients found the median free fraction of valproate (percentage of drug not bound to albumin) was 48% (range 15–89%), and no patient had an expected valproate free fraction of 5–10% .…”
Section: Valproatementioning
confidence: 99%
See 3 more Smart Citations